Socialization of the Utilization of Gamma-App Technology as an Effective Strategy in English Learning at SMP Jejakaka in Dobo, Aru Islands - Que, Stella R; Kahar, Siti Rahmawati; Ulorlo, Yulia Josina; Apalem, Corneles Rubenaser; Hasyim, Gama Rani; Gurguren, Jesica Mersiana; Sambonu, Sarti Leoni (Civiliza Publishing, 2024)
The program aims to introduce the utilization of Gamma-App as an effective method of teaching English at SMP Jejakaka in Dobo, Aru Islands. The activity was carried out as a solution to barriers in learning English in isolated areas, which include the limitations of innovative learning media and the lack of motivation of students. This service involves training for teachers on how to use Gamma-App in the teaching process as well as evaluation of its implementation. The results of the activities showed a significant improvement in teachers' ability to use Gamma - App as an interactive learning medium, with an 85% increase in teachers' understanding. Through this dedication, the use of Gamma-App proved to be strategically innovative to improve the quality of English language learning in remote locations. It is hoped that this activity will serve as an example for other schools in applying technology to create inclusive, interactive, and effective learning.